Developing Creative “Spaces” in Libraries for Creative Tourism - Lavranos, Charilaos; Vouvaki-Manousaki, Christina; Kostagiolas, Petros (Qualitative and Quantitative Methods in Libraries, 2020)
Tourism is an interdisciplinary, economic and social phenomenon, directly linked to the promotion of cultural heritage. Creative tourism involves the active participation of the visitor in various cultural activities, contributing to the enjoyment of the tourist experience from the perspective of experiential interaction, as well as linking tourism to the economic, social and cultural development of a destination. Through creative tourism activities and interactive participation in cultural actions, visitors have the opportunity to develop their creative skills. Libraries, as organisations that are linked to the promotion of the cultural heritage of a place, present opportunities to take part in the actions of creative tourism developing creative “spaces” for tourism purposes. This paper focuses on the presentation of creative tourism innovative activities related to the promotion, diffusion and their integration in the function of libraries through the development of creative “spaces”. Through this work we strive to better understand how libraries as creative “spaces” provide opportunities for many forms of cultural participation, especially in the tourism sector, developing creativity in tourism experiences. The significance and originality of the current study reside in exploring the interrelations of creative tourism facets to libraries’ function.